2021
DOI: 10.1088/1361-6641/ac02da
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and reduction of RF loss induced by Al diffusion at the AlN/Si(111) interface in GaN-based HEMT buffer stacks

Abstract: GaN-based high electron mobility transistors (HEMT) on Si (111) substrates have large potential for applications in the 5G telecommunication field. However, for this potential to be fully realized, all loss mechanisms need to be minimized. It is known that typical metal-organic chemical vapor deposition (MOCVD) processes used to grow the GaN epitaxial layers can cause considerable parasitic conductivity at the interface of the AlN nucleation layer to the high-resistivity Si substrate, leading to reduced gain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…25−28 In order to further confirm these results, transmission electron microscopy (TEM) experiments were performed. Panels (a and b) and (c and d) in Figure 1 show the bright-field TEM images under two-beam conditions with g = [0002] and g = [11][12][13][14][15][16][17][18][19][20] for sample A (with conventional pretreatment conditions) and sample E, respectively. It is again shown that both screw-and edge-type threading dislocations in sample E are significantly reduced compared to those in sample A.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…25−28 In order to further confirm these results, transmission electron microscopy (TEM) experiments were performed. Panels (a and b) and (c and d) in Figure 1 show the bright-field TEM images under two-beam conditions with g = [0002] and g = [11][12][13][14][15][16][17][18][19][20] for sample A (with conventional pretreatment conditions) and sample E, respectively. It is again shown that both screw-and edge-type threading dislocations in sample E are significantly reduced compared to those in sample A.…”
Section: Resultsmentioning
confidence: 99%
“…The dislocation density, as well as the RF loss, is among the lowest level reported so far in the literature for GaN-on-Si, as shown in Figure 5d. [19][20][21]34,47 These results indicate the promising potential of the USAP technique and make it beneficial for GaN-on-Si RF applications.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations